THE “HUASO RAIMuNDO’S GANGS”. SOCIAL NETWORKS AND DELICTIVE TRANSITIONALITY IN SANTIAGO AND ITS SURROuNDINGS (1882-1911) - Ayala Cordero, Ignacio (Revista de Historia Social y de las Mentalidades, 2024)
As known thief, Nonato Orellana Aviles  appears as a transitional subject in the  context of capitalist modernization in  Chile. Represents the process of claim  depeasantization and disciplining of  rural peonage, in addition to the forms  of incorporation into the city from the  transgression. Transitionality expression is  also the diversity of media documentaries  crimes that had as protagonist in a space of  time ranging from 1904 to 1911. The objective of this article is to analyze,  incorporating micro-historical approach  and social network analysis, the practice  developed by criminal “Huaso Raimundo’s  gangs” from strategic and organizational  dimensions. While day survival strategy,  not subordinated to the work ethic, be an  alternative to proletarianization; while  through its organizational features, such  strategy would be designed socially  incorporated in the process of setting up the  “criminal underworld” of Santiago and its  surroundings.
Keywords: social networks; delictive transitionality; social criminality